2006
DOI: 10.1111/j.1365-2036.2006.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: bacterial translocation in the critically ill – evidence and methods of prevention

Abstract: Summary Background Delayed sepsis, systemic inflammatory response syndrome (SIRS) and multiorgan failure remain major causes of morbidity and mortality on intensive care units. One factor thought to be important in the aetiology of SIRS is failure of the intestinal barrier resulting in bacterial translocation and subsequent sepsis. Aim This review summarizes the current knowledge about bacterial translocation and methods to prevent it. Methods Relevant studies during 1966–2006 were identified from a literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 186 publications
(214 reference statements)
3
121
0
15
Order By: Relevance
“…Obstructive jaundice is almost universally believed to promote bacterial translocation. Absence of bile from the lumen of gut is also associated with a quantitative increase in small intestinal microflora [18] . Translocation from the intestine is most commonly detected by measuring the presence of viable bacteria in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive jaundice is almost universally believed to promote bacterial translocation. Absence of bile from the lumen of gut is also associated with a quantitative increase in small intestinal microflora [18] . Translocation from the intestine is most commonly detected by measuring the presence of viable bacteria in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Three primary mechanisms promote BT from the gastrointestinal tract: (a) intestinal bacterial overgrowth, (b) immunodeficiencies, and (c) increased intestinal permeability [5,24]. BT may cause the ingress of viable bacteria and their antigens with the development of sepsis, initiation of the cytokines mediated multiorgan dysfunction syndrome (MODS), systemic inflammatory response syndrome (SIRS), and death [10]. Probiotics are defined as non-pathogenic live microorganisms that seem to promote gut health and regulate intestinal homeostasis [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…(21) Several studies have shown an association between dysfunction of intestinal motility and bacterial proliferation. (23)(24)(25)(26) In an experimental study Nieuwenhuijs et al compared infusion of morphine with placebo.…”
Section: Bacterial Translocationmentioning
confidence: 99%
“…(21) Inflammatory mediators can increase intestinal permeability without necessarily damaging the mucosa. Cytokines may act as modulators of these structures and may thus increase permeability to antigens that promote onset of an intestinal inflammatory cascade.…”
Section: Bacterial Translocationmentioning
confidence: 99%